2009
DOI: 10.1371/journal.pone.0004401
|View full text |Cite
|
Sign up to set email alerts
|

CLSI-Derived Hematology and Biochemistry Reference Intervals for Healthy Adults in Eastern and Southern Africa

Abstract: BackgroundClinical laboratory reference intervals have not been established in many African countries, and non-local intervals are commonly used in clinical trials to screen and monitor adverse events (AEs) among African participants. Using laboratory reference intervals derived from other populations excludes potential trial volunteers in Africa and makes AE assessment challenging. The objective of this study was to establish clinical laboratory reference intervals for 25 hematology, immunology and biochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
221
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(279 citation statements)
references
References 21 publications
41
221
16
1
Order By: Relevance
“…White Blood Cell (WBC) components A high proportion of participants in the African studies have WBC counts below the lower range of the Massachusetts General Hospital US population-derived values [9,20]. This phenomenon is consistent with a number of studies that have reported lower WBC counts in…”
Section: Laboratory Reference Intervals In Africa 309supporting
confidence: 82%
See 3 more Smart Citations
“…White Blood Cell (WBC) components A high proportion of participants in the African studies have WBC counts below the lower range of the Massachusetts General Hospital US population-derived values [9,20]. This phenomenon is consistent with a number of studies that have reported lower WBC counts in…”
Section: Laboratory Reference Intervals In Africa 309supporting
confidence: 82%
“…(MCH) by gender have been observed in several African studies, with adult males having higher values than adult females in East Africa [9,16,20,31,39,40], Southern Africa [20,36], West Africa [41] and Central Africa [42]. These gender differences in RBC parameters as illustrated in our findings (Table 2), are consistent with previously established evidence that males have higher values than females for these parameters and is partly attributed to the influence of the androgen hormone on erythropoiesis [43,44] and to menstrual blood loss in women [16,25,39,42,45].…”
Section: Laboratory Reference Intervals In Africa 309mentioning
confidence: 96%
See 2 more Smart Citations
“…In a survey of men and women who were healthy by history and physical examination, from potential vaccine trial populations, 10-35% of volunteers would not be eligible. 103,104 However, data from current PrEP testof-concept trials may allow these criteria to be less stringent.…”
mentioning
confidence: 99%